Beiträge zum Wortschatz des Alten Testaments: Das Hapax legomenon fetiygiyl in Jesaja 3,24 - Theis, Christoffer (Vetus Testamentum, 2022)
In Isa 3:24 there is a hapax legomenon פְּתִיגִיל, which so far could not be explained convincingly. This short note suggests to explain the word’s etymology from Napatan tgr “chain” in combination with the Egyptian article pꜣ.